Channel Water Storage Anomaly: A New Remotely Sensed Quantity for Global River Analysis. Issue 1 (3rd January 2023) - Coss, Stephen; Durand, Michael T.; Shum, C. K.; Yi, Yuchan; Yang, Xiao; Pavelsky, Tamlin; Getirana, Augusto; Yamazaki, Dai
Abstract: River channels store large volumes of water globally, critically impacting ecological and biogeochemical processes. Despite the importance of river channel storage, there is not yet an observational constraint on this quantity. We introduce a 26‐year record of entirely remotely sensed volumetric channel water storage (CWS) change on 26 major world rivers. We find mainstem volumetric CWS climatology amplitude (CA) represents an appreciable amount of basin‐wide terrestrial water storage variability (median 2.78%, range 0.04%–12.54% across world rivers), despite mainstem rivers themselves represent an average of just 0.2% of basin area. We find that two global river routing schemes coupled with land surface models reasonably approximate CA (within ±50%) in only 11.5% (CaMa‐Flood) and 30.7% (HyMap) of rivers considered. These findings demonstrate volumetric CWS is a useful quantity for assessing global hydrological model performance, and for advancing understanding of spatial patterns in global hydrology. Plain Language Summary: Rivers are a critical part of global hydrology, but until now the variation in how much water rivers store has not been observed directly (via a measurement based approach) on the global scale. Surface water storage and fluxes are critical in understanding the impacts and trajectory of global climate change. We created a 26 years record of this quantity across 26 of the world's largest rivers. We found that the storage variation in river main channels can represent up to 12.54% of the total water storage variation in a river basin despite only representing 0.2% of the total surface area. We also find that the only previous method to estimate this quantity, through modeling (global river routing schemes coupled with land surface models), represent this quantity within 50% of our estimated value on between just 11.5%–30.7% of the rivers we studied. Our work shows that this quantity is a substantial land surface hydrology storage term, and also demonstrates a critical need for the inclusion of more measurement based data to improve model performance. Global models are our best tool for understanding global climate change and data sets like this one can help improve their accuracy. Key Points: We introduce a 26‐year record of entirely remotely sensed volumetric channel water storage anomaly Storage climatology amplitude represents (0.04%–12.54%) terrestrial water storage variability but just 0.2% of basin area This new quantity provides a physical grounding for land surface hydrology models that are critical for the water cycle